Fatigue life testing and analysis of remanufactured components - Dinesh s/o Cheram (2014)
High strength steels such as AISI 4340 are extensively used in many industrial applications such as building and construction, automobiles and aircraft applications. However, like other steels, 4340 steels are highly susceptible to fatigue failure. Therefore, the fatigue analysis of 4340 steels is crucial due to its extensive and rapidly increasing usage in industrial applications. In addition, there is a need for remanufacture engineering as the replacement of 4340 steel components is costly and impractical. In this project, un-notched and notched 4340 steel specimens are fatigue tested under various stress ranges to deduce the lifespan of 4340 steels and the S-N curves are plotted. The fatigue crack growth rates of notched 4340 steels are also studied extensively by various techniques such as Scanning Electron Microscopy (SEM) and Digital Imaging Correlation (DIC). The Paris law constants m and C are empirically derived from results obtained from fatigue crack growth rates and the stress intensity factor ahead of the crack tip. In the final experiment, laser cladded 4340 steels which simulate remanufactured components are fatigue tested. Subsequently, microstructural evaluation on the fractured surface of laser cladded 4340 steels are conducted by SEM analysis to identify fatigue initiation sites and fatigue failure mechanisms.